Pengaruh Iklim Komunikasi Organisasi Terhadap Kinerja Pegawai Pada Bagian Humas Kabupaten Sragen - Rahmawati, Erna, Drs. Joka Sutarso, S.E., M.SiJOKO (2017)
Creating good organizational communication atmosphere needs the understanding of the matter and also staff condition. In organization, communication atmosphere plays very significant role in encouraging the members of the organization to give their attention to the organization including the change of the organizational system which can lead to the positive effect to the atmosphere of the organizational communication. The problem rises whether the atmosphere influences the performance of the staff. The atmosphere of the organizational communication can influence the staff's performance. Besides, the environment of the workfield also influence the productivity and the achievement of staff. This reserach applied correlational method with quantitaive approach. A correlational method is a kind of reserach method which studies the correlation among variables. Data in this research were taken through questionnaire to 40 respondents which were choosen as samples, field observation, and document or archieves which were relevants with this research. The analysis of the data used simple regression analysis, F test. The result of the research showed that there was positive and significant impact of the organizational communication atmosphere to the performance of the staff of PR division of the governance of Sragen interpeted by regression equation of Y = 28.025 + 0.664X. it meant organizational communication atmosphere had positive and effect so that when the organizational communication increased, the performance of the staff also moved up